Responsible management understanding human nature, ethics, and sustainability - Ogunyemi, Kemi. (2013 digital library., 2013)
This book serves as a valuable complementary text for courses on Ethics, Responsibility, Leadership, Corporate Social Responsibility, and Sustainability, which mostly tend to neglect their human nature dimensions. It provides an understanding of human nature and its uniqueness and complexity, which helps managers in today's business world to better manage and to respect self, others, and the environment. It also provides the foundation for learning ethical behavior, leadership, responsibility, sustainable management, and corporate social responsibility. Without this angle, an MBA might tend to focus primarily on financial success in different dimensions--operational quality, financial strategy, workforce motivation, cost-cutting strategies, etc. and people may forget to take cognizance of the implications of their own nature and that of the people through whom they have to work. Future leaders and shapers of sustainable organizations and societies cannot afford to have such a knowledge gap. Having these discussions helps students understand that the reason to be ethical goes beyond self-interest and profit motives to the very foundations of human nature.